Implementasi Re-design UI/UX Website Fumigasi Untuk Meningkatkan Customer Experience - Faisal Maulana Akbar; Ayouvi Poerna Wardhanie2; Tan Amelia (Indonesian Society of Applied Science, 2023)
Fumigation website is a website owned by PT. Prana Argentum which is used as a platform for disseminating information related to pest control. However, based on interviews with company owners, there are some drawbacks such as the appearance of the website is not very user friendly, the information provided is difficult to find. This is also supported by the results of the UEQ pre-survey of website users, where the results of the 6 UEQ scale get the